Strategic internationalisation of firms from developing nations: Case of Tata motors - Tibrewala, Sanchi (2010)
Internationalisation is not a new phenomenon as firms have been internationalising in pursuit of opportunities in international market for a long time now. But the current wave of internationalisation is exhibiting a slightly different nature as compared to the previous waves; now the firms from the developing nations are increasingly internationalising particularly to the developed markets. Information technology has lowered the barriers and has helped firms reduce psychic distance which have increased entrepreneurial activity in the firms from the developing nations. This dissertation investigates the internationalisation process of Tata enterprises, an Indian conglomerate. Using semi structured interviews this research investigates the factors leading to internationalisation of Tata enterprises, the challenges faced during the process and finally the possible future scenarios for Tata‟s internationalisation process. This research finds that Tata‟s internationalisation was led by both motivation for accessing the lucrative emerging markets for selling the products and accessing developed markets for their innovation capabilities. The factors leading to internationalisation of Tata and challenged faced during the process are similar to the findings of the previous research which was conducted mainly in developed nations. This research thus finds, that internationalisation of firms from developing nations exhibit the same characteristics as internationalising firms from the developed nations. The former tend to ensure their stability in the domestic market before internationalizing while the later may seek internationalisation as an alternative to domestic market dominance.